Birth cohort and the black-white achievement gap: The roles of health soon after birth - Kenneth Y. Chay; Jonathan Guryan; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2009)
One literature documents a significant, black-white gap in average test scores, while another finds a substantial narrowing of the gap during the 1980's, and stagnation in convergence after. We use two data sources - the Long Term Trends NAEP and AFQT scores for the universe of applicants to the U.S. military between 1976 and 1991 - to show: 1) the 1980's convergence is due to relative improvements across successive cohorts of blacks born between 1963 and the early 1970's and not a secular narrowing in the gap over time; and 2) the across-cohort gains were concentrated among blacks in the South. We then demonstrate that the timing and variation across states in the AFQT convergence closely tracks racial convergence in measures of health and hospital access in the years immediately following birth. We show that the AFQT convergence is highly correlated with post-neonatal mortality rates and not with neonatal mortality and low birth weight rates, and that this result cannot be explained by schooling desegregation and changes in family background. We conclude that investments in health through increased access at very early ages have large, long-term effects on achievement, and that the integration of hospitals during the 1960's affected the test performance of black teenagers in the 1980's.
Keywords: 330; Weiße; Farbige Bevölkerung; Kognition; Test; Gesundheitsvorsorge; Kinder; USA